Program Pembentukan Akhlak Siswa Pada Masa Pubertas (Studi Kasus di SMP Tri Bhakti Tegaldlimo Banyuwangi Tahun Pelajaran 2018/2019 - Ervin Sanika; Fathi Hidayah (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2018)
School as an institution that is obliged to guide students to be strong, morally and hardworking must have breakthroughs in developing student morals, especially for the school level where students are in puberty. The activity carried out by Tri Bhakti Tegaldlimo Banyuwangi Middle School as an effort to assist students through puberty is a complete package because it is done through several methods. Habitual methods through religious activities, additional knowledge insights around puberty, and mentoring activities of talent and interest skills. In addition to the form of habituation, also do not forget to be provided with an example by the teacher through disciplinary activities and the most important thing is giving advice. These methods are the answers to the problems of today's youth education. Schools as parents do not only cram students with various forms of theoretical discourse, but also provide facilities as forming the moral virtues of their students.